Endonuclease A in Streptococcus pneumoniae: escaping from neutrophil extracellular traps (NETs) and relationship in immunogenicity - Marina Yusoff; Chew Chieng Yeo; Muhammad Hassan Nasir; Malik Amonov (Open Exploration Publishing Inc., 2024)
Streptococcus pneumoniae (S. pneumoniae), which is a Gram-positive diplococcus, has emerged as a significant human pathogen. It is a primary cause of bacterial pneumonia, otitis media, meningitis, and septicemia, leading to a considerable impact on global morbidity and mortality. The investigation of S. pneumoniae and its virulence factors has resulted in the identification of surface endonuclease A (EndA). EndA functions in DNA uptake during natural transformation and plays a significant role in gene transfer. The ability of S. pneumoniae to degrade neutrophil extracellular traps (NETs) enhances its virulence and invasive potential in pneumococcal infections. NETosis occurs when neutrophils release chromatin into the extracellular space to form NETs, capturing and neutralizing pathogens. Currently, NETosis can be induced by several microbes, particulate matter, and sterile stimuli through distinct cellular mechanisms, and this includes the involvement of EndA in S. pneumoniae. Here, we reviewed the cellular functions of EndA, its role in S. pneumoniae as a virulence factor in relation to NETosis, its relationship to immunogenicity, and its involvement in several diseases. The discovery of this relationship would significantly impact therapeutic technology in reducing disease burden, especially pneumococcal infections.